Enhancing Distance Education Resilience: Developing a Scale for Effective Implementation During Global Crises - Kizil, Ibrahim; Kizil, Fatima Seyma; Jang, Bong Gee (International Review of Research in Open and Distributed Learning, 2025)
The global shift to distance education during the COVID-19 pandemic challenged the resilience and efficiency of educational systems worldwide. This study investigated the factors influencing the effectiveness and resilience of distance education in elementary schools in Türkiye. Using a quantitative method, 100 elementary school teachers from various regions of Türkiye were surveyed. Guided by the technology acceptance model (TAM) and employing exploratory factor analysis (EFA), the study identified four critical factors: (a) teachers’ prior knowledge and experience with distance education; (b) perspectives on the Educational Informatics Network (EIN); (c) stakeholder support; and (d) technology integration knowledge and experience. The findings emphasized the role of comprehensive teacher training programs in equipping educators to adapt to digital teaching environments. They also underlined the importance of national educational platforms like EIN, which served as a critical resource during the pandemic. Collaborative support systems involving school administration, parents, and technical teams were found to significantly enhance the success of distance education. Furthermore, teachers’ ability to integrate technology into their teaching practices emerged as a crucial factor. These results have significant implications for educational policy, and highlight the need for a multidimensional strategy to strengthen distance education systems and ensure their resilience during global crises.